Capacitance tomography technique for imaging mixture oil and water - Mohamad Talib, Masturah Tunnur (2012)
Electrical Capacitance Tomography (ECT) sensor is non-invasive device that used the Electrical Capacitance Tomography Techniques which is non - intrusive technique to measure the concentration of flow inside the pipeline. By develop 12 ECT sensors with MATLAB programming software, the distribution of fluids inside pipeline or vessel can be visualized easily. By design a simple 12 ECT sensor with portable electrodes may reduce the difficulties on sensor construction and configuration. Perhaps that, this project can give some idea to anyone out there to develop better ECT system in practice. This system also can be used to investigate volume ratio of mixture oil and water particularly in horizontal-stratified distribution inside a flowing pipeline. Data from hardware system can be computed using MATLAB software in order to visualize the cross-section image of pipeline. Linear Back projection algorithm is taken in to account as a projection method use in this project.